Microbiological and Biochemical Characteristics of Tradition Dairy Product: Identification of Dominant Lactobacillus - Arokiyamary, A (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTA total of 27 strains were isolated from 5 Traditional Dairy Products samples that were collected in Pondicherry. The Lactic acid bacteria (LAB) dominated the Microbial Population of Dairy Samples and were identified on basis of their morphological, physiological and biochemical characteristics. Among the isolates, the Lactobacillus LBC216 was predominant. The distribution of the isolates by was as follows; Lactobacillus spp LBC 216 (10%), LBL 217 (4%), LBB 218 (2%), LHB 219 (2%), LBF 220 (2%). The five representative Lactobacillus spp were identified to species level in carbohydrate pattern according to Bergey’s Manual. The identified strains were then evaluated for some technological properties. One strain Lactobacillus LBC 216 only had antagonistic properties against Staphylococcus aureus and Bacillus cereus.